Analysis of performances of European Championship participants among women’s wrestling cadets - Латышев, Николай; Рыбак, Леонид; Головач, Инна; Королев, Борис; Ляшенко, Елена; Квасница, Олег (Slobozhanskyi Herald of Science and Sport, 2019)
Mykola Latyshev, Leonid Rybak, Inna Holovach, Borys Korolov, Olena Liashenko & Oleh Kvasnytsya Purpose: to analyze the sports achievements of the participants of the European Championships among cadets in women’s wrestling for the national team of Ukraine. Material & Methods: analyzed the sports careers of 74 athletes of the Ukrainian team, who took part in the European Championship among cadets from 2000 to 2010, and their further performances to date. Results: the following indicators are considered: the results of the athletes ’performances at the European Championship among cadets; the number of athletes who continued their careers separately in junior and adult years; results of the performance of athletes in junior and adulthood at international competitions. Conclusions: the general trends of the future career and achievements of the athletes of the national team of Ukraine who participated in the European Championships among cadets from 2000 to 2010 are revealed. For athletes established the relationship of their own results at all stages of a sports career. Quantitative data and distribution of characteristics for all 74 participants of the competition are given: 56.8% of female athletes continued their career among adults, and 24.3% took prizes in European and world championships. An outstanding result is emphasized - five athletes managed to take part in the Olympic Games.